Transdisciplinarity and creativity in the teaching of literature - RAÏSSI- DJERAFI , Loubna (Journal of Human Sciences, 2023)
As Trainers of trainers, we must prepare learners as well as possible for a future that is changing exponentially. The activities we offer them aim to decompartmentalize the learning of a foreign language from the communicative tool and language skills towards an artistic and holistic approach. These activities promote learning experiences that affect the whole and the core of our creative being, our imagination. However, it is not because we appeal to the sensitive elements of the learner that we forget or leave aside the know-how close to cognition.As part of this research work, we aim to determine to what extent the support for the discovery and invention of new instructions resulting from the readings carried out facilitates inspiration and leads learners to the creative act.